A cluster randomised feasibility trial of clinically assisted hydration in cancer patients in the last days of life. (April 2018) - Davies, Andrew N; Waghorn, Melanie; Webber, Katherine; Johnsen, Sigurd; Mendis, Jeewaka; Boyle, Julia
Background: The provision of clinically assisted hydration at the end-of-life is one of the most contentious issues in medicine. Aim: The aim of this feasibility study was to answer the question 'can a definitive (adequately powered) study be done?' Design: The study was a cluster randomised trial, with sites randomised on a one-to-one basis to intervention 'A' (regular mouth care and usual other care) or intervention 'B' (clinically assisted hydration, mouth care and usual other care). Participants were assessed every 4 h, and data collected on clinical problems, therapeutic interventions and overall survival. Setting/participants: The study was conducted at 12 sites/'clusters' with specialist palliative care teams (4 cancer centres and 8 hospices), and participants were cancer patients in the last week of life who were unable to maintain sufficient oral fluid intake. Results: The study achieved its pre-determined criteria for success. Two hundred patients were recruited to the study, and 199 participants completed the study, over a 1-year period. A total of 38.5% participants discontinued clinically assisted hydration due to adverse effects: none of these adverse events were rated as 'severe' or worse in intensity. The primary reasons for discontinuation were site problems ( n = 2), localised oedema ( n = 13), generalised oedema ( n = 5), respiratory secretions ( n = 6) and nausea and vomiting ( n = 1). Conclusion: The results of this feasibility study suggest that a definitive study can be done, but that minor changes are needed to the protocol to standardise the administration of clinically assisted hydration (which may reduce the incidence of certain adverse effects).